2023
DOI: 10.1002/anie.202304051
|View full text |Cite
|
Sign up to set email alerts
|

A Route to Stabilize Uranium(II) and Uranium(I) Synthons in Multimetallic Complexes

Abstract: Herein, we report the redox reactivity of a multimetallic uranium complex supported by triphenylsiloxide (−OSiPh3) ligands, where we show that low valent synthons can be stabilized via an unprecedented mechanism involving intramolecular ligand migration. The two‐ and three‐electron reduction of the oxo‐bridged diuranium(IV) complex [{(Ph3SiO)3(DME)U}2(μ‐O)], 4, yields the formal “UII/UIV”, 5, and “UI/UIV”, 6, complexes via ligand migration and formation of uranium‐arene δ‐bond interactions. Remarkably, complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 105 publications
5
13
0
Order By: Relevance
“…The U1 ion no longer interacts with the planar arene anchor [1.390(5)–1.404(5) Å], and the U1–C centroid distance [3.813(2) Å; Table ] is significantly longer than the U1–C centroid distances found in the previously reported U(IV) terminal oxo, [K(2.2.2-cryptand)][(( Ad,Me ArO) 3 mes)U(O)] [2.810(6) Å], and U(IV) halide, [(( Ad,Me ArO) 3 mes)U(X)(THF)] (where X = F; 2.666, Cl; 2.657, Br; 2.645, and I; 2.664 Å), tris(aryloxide) mesitylene complexes. , The N1–N2 [1.458(4) Å] and U1–N PhNNPh bond distances [2.283(3) and 2.310(3) Å] of the dianionic [PhNNPh] 2– moiety are consistent with the bond metrics found in the only other dianionic U(IV)–PhNNPh example, [K(2.2.2-cryptand)][U(PhNNPh)(N(SiMe 3 ) 2 ) 3 ] . The N1–N2 bond length [1.458(4) Å] is similar to that reported for the salt, [K(18C6)] 2 [PhNNPh] [1.40(3) Å], and is elongated compared to PhNNPh (1.25 Å) and to the singly reduced derivative, [K(2.2.2-cryptand)][PhNNPh] [1.34(3) Å], obtained from the reaction of the only isolated U(I) complex with azobenzene …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The U1 ion no longer interacts with the planar arene anchor [1.390(5)–1.404(5) Å], and the U1–C centroid distance [3.813(2) Å; Table ] is significantly longer than the U1–C centroid distances found in the previously reported U(IV) terminal oxo, [K(2.2.2-cryptand)][(( Ad,Me ArO) 3 mes)U(O)] [2.810(6) Å], and U(IV) halide, [(( Ad,Me ArO) 3 mes)U(X)(THF)] (where X = F; 2.666, Cl; 2.657, Br; 2.645, and I; 2.664 Å), tris(aryloxide) mesitylene complexes. , The N1–N2 [1.458(4) Å] and U1–N PhNNPh bond distances [2.283(3) and 2.310(3) Å] of the dianionic [PhNNPh] 2– moiety are consistent with the bond metrics found in the only other dianionic U(IV)–PhNNPh example, [K(2.2.2-cryptand)][U(PhNNPh)(N(SiMe 3 ) 2 ) 3 ] . The N1–N2 bond length [1.458(4) Å] is similar to that reported for the salt, [K(18C6)] 2 [PhNNPh] [1.40(3) Å], and is elongated compared to PhNNPh (1.25 Å) and to the singly reduced derivative, [K(2.2.2-cryptand)][PhNNPh] [1.34(3) Å], obtained from the reaction of the only isolated U(I) complex with azobenzene …”
Section: Resultsmentioning
confidence: 99%
“…Twoelectron redox reactivity was reported for the reduced complexes, but the involved ligand rearrangement limited the system versatility. 45 Considering the ability of siloxide ligands to stabilize uranium in low oxidation states, 38,45,46 their high stability both in reducing 47 and oxidizing conditions, 7,10,46 and their ability to support original reactivity with small molecules, 38,48,49 we reasoned that a tris(siloxide) arene-anchored tripodal ligand may allow access to lower oxidation states while promoting unprecedented redox-reactivity. Indeed, we very recently showed that the tris(tert-butoxy)siloxide arene can stabilize cerium complexes in four states of charge.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 This is despite theoretical studies on bis-benzene actinide complexes, 14–16 and also matrix isolation experiments with actinide atoms and aromatic molecules. 17 The growing family of molecules which leverage (tethered) uranium–arene linkages as electron reservoirs to stabilize unusual formal oxidation states, 18–23 along with recent extension of these works to the transuranium elements neptunium and plutonium, 24 make a clear case for the development of a modern theoretical description of the uranium–arene interaction to provide insight into future synthetic work and as a starting point for further transuranium research. Herein we have compared variants of [U(arene)(BH 4 ) 3 ] where arene = C 6 H 6 ; C 6 H 5 Me; C 6 H 3 -1,3,5-R 3 (R = Et, iPr, t Bu, Ph); C 6 Me 6 ; and triphenylene (C 6 H 4 ) 3 in both terminal and central ring-bound configurations by density functional theory (DFT) and multireference complete active space methods (CASPT2).…”
Section: Introductionmentioning
confidence: 99%
“… This complex adopts a bent metallocene geometry with a Cnt–Ba–Cnt (Cnt = ring centroid) angle of 130.7° and has two arene rings oriented toward the barium metal center in an η 2 -fashion . Given that there is precedent for the stabilization of reduced uranium complexes through U–arene interactions, the use of phenylsilyl-substituted tetramethylcyclopentadienyl ligands could be an attractive method to synthesize new examples of low oxidation state uranium complexes.…”
Section: Introductionmentioning
confidence: 99%